Knowledge Retention Strategy and Performance of Small And Medium Enterprises in Ado-Ekiti Metropolis - Olalekan, Enitilo; Awolaja, Ayodeji Muyideen; Otulana, Olumayowa Kabir (International Journal of Business, Management and Economics, 2023)
The study looked at the performance of small and medium-sized businesses in Ado-Ekiti Metropolis and their knowledge retention strategy. The study took the form of a descriptive survey research design. The study’s participants were 11,663 owners and managers of small and medium-sized businesses in the Ado-Ekiti Metropolitan Area. Yamane was used to collect 387 samples (1967). The study’s primary data was collected via a standardised questionnaire. Regression was used to examine the data collected. The findings show that all of the explanatory factors’ constructs have a significant impact on the performance of small and medium-sized businesses in Ado-Ekiti Metropolis.